A Literature Review of Geographic Representation in Adult Education Research - Angela Kissel (Adult Education Research Conference, 2024)
The purpose of this literature review is to determine how adult education research is geographically represented by topic and population in three adult education journals from 1998 through 2023.
Keywords: Adult education; spatial; geography; critical spatial analysis; spatial justice